2021
DOI: 10.1371/journal.pone.0258578
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of pregnancy self-testing among pregnant women attending antenatal care in western Kenya

Abstract: In sub-Saharan Africa little is known about how often women use pregnancy self-tests or characteristics of these women despite evidence that pregnancy self-testing is associated with early antenatal care (ANC) initiation. Understanding the characteristics of women who use pregnancy self-tests can facilitate more targeted efforts to improve pregnancy testing experiences and entry into the ANC pathway. We conducted a cross-sectional survey among pregnant women enrolling in a pre-exposure prophylaxis (PrEP) imple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Some women did not know they could use a home pregnancy test to confirm their pregnancies, consistent with prior findings from a preliminary survey ( 1 ). These women may have had limited exposure to messages reinforcing home pregnancy test use through local media platforms, school education, friends, partners, or other community sensitization efforts.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Some women did not know they could use a home pregnancy test to confirm their pregnancies, consistent with prior findings from a preliminary survey ( 1 ). These women may have had limited exposure to messages reinforcing home pregnancy test use through local media platforms, school education, friends, partners, or other community sensitization efforts.…”
Section: Discussionsupporting
confidence: 75%
“…Urine home pregnancy tests were introduced to the global market in the 1970s and continue to provide women with an easy and discrete way to assess their pregnancy status ( 18 ). However, there are limited data on home pregnancy test use in western Kenya, and in one study, few women reported using home pregnancy tests in early pregnancy ( 1 ). This study aimed to understand why women who had previously attended antenatal care at public health facilities in Homa Bay and Siaya counties did not initially use home pregnancy tests to confirm their pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations